Adolescent Exposure to Violence and Adult Anxiety, Depression, and PTSD. (June 2020) - Covey, Herbert C.; Grubb, Leah McCoy; Franzese, Robert J.; Menard, Scott
The present study investigates how adolescent exposure to violence (AEV), in the form of parental physical abuse, witnessing parental violence, and exposure to violence in the neighborhood, is related to adult anxiety, depression, and post-traumatic stress disorder, controlling for more general adolescent violent victimization and for self-reports and parent reports of mental health problems in adolescence, on a national household-based probability sample of individuals who were adolescents in the mid-1970s and who were followed through early adulthood in the early 2000s. The results suggest that AEV is associated with mental health problems in adolescence but not, controlling for other variables, in adulthood, but there is continuity in mental health problems associated with AEV from adolescence to adulthood.